2018
DOI: 10.1001/jamaophthalmol.2018.1719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anticholinergic Drug Use With Risk for Late Age-Related Macular Degeneration

Abstract: IMPORTANCE Amyloid-β is a major component of retinal drusen, the primary lesions of age-related macular degeneration (AMD), and autopsy and animal models suggested that anticholinergic drug (ACD) use increased brain amyloid-β deposition. OBJECTIVE To investigate the association between exposure to ACDs and late AMD (features of neovascular AMD or geographic atrophy of the retinal pigment epithelium in at least 1 eye). DESIGN, SETTING AND PARTICIPANTS A multicenter case-control study in 4 French ophthalmologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The 104 validation studies consisted of 1 RCT (good quality) [ 98 ], 74 cohort studies (50 good and 24 poor quality) [ 33 – 36 , 41 , 44 , 54 , 55 , 57 , 59 , 61 66 , 70 75 , 77 , 78 , 80 , 81 , 83 97 , 100 , 103 108 , 112 115 , 117 , 119 , 120 , 123 , 124 , 129 , 131 137 , 139 , 141 146 , 148 , 149 ], 9 case-control studies (6 good, 1 fair and 2 poor quality) [ 56 , 67 69 , 102 , 110 , 118 , 130 , 147 ] and 20 cross-sectional studies (2 good and 18 poor quality) [ 39 , 53 , 58 , 60 , 76 , 79 , 82 , 99 , 101 , 109 , 111 , 116 , 121 , 122 , 125 128 , 138 , 140 ] (Appendix 6 ). More than half of the studies were judged to be of good quality (60 out of 104).…”
Section: Resultsmentioning
confidence: 99%
“…The 104 validation studies consisted of 1 RCT (good quality) [ 98 ], 74 cohort studies (50 good and 24 poor quality) [ 33 – 36 , 41 , 44 , 54 , 55 , 57 , 59 , 61 66 , 70 75 , 77 , 78 , 80 , 81 , 83 97 , 100 , 103 108 , 112 115 , 117 , 119 , 120 , 123 , 124 , 129 , 131 137 , 139 , 141 146 , 148 , 149 ], 9 case-control studies (6 good, 1 fair and 2 poor quality) [ 56 , 67 69 , 102 , 110 , 118 , 130 , 147 ] and 20 cross-sectional studies (2 good and 18 poor quality) [ 39 , 53 , 58 , 60 , 76 , 79 , 82 , 99 , 101 , 109 , 111 , 116 , 121 , 122 , 125 128 , 138 , 140 ] (Appendix 6 ). More than half of the studies were judged to be of good quality (60 out of 104).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed that T2DM patients treated with metformin, older patients, and having a higher DCSI score linked to an increased risk of AMD. Previous studies have identified several risk factors for AMD, including aging, ocular disorders, systemic diseases, smoking, diet, genetic susceptibility, and environmental risk factors ( Lim et al, 2012 ), with aging being the strongest risk factor ( Aldebert et al, 2018 ). In the general population, vitamin B12 plasma levels decline with age, and thus, the prevalence of vitamin B12 deficiency increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…
The global prevalence of AMD in 2020 is projected to be 196 million people [1] and that of Alzheimer's disease was 50 million in 2017 [2]. Chronic oxidative stress and neuroinflammation from aging, injury, and individual risk factors (smoking, hypertension, arteriolosclerosis, obesity, dietary indiscretion, chronic anticholinergic use, and latent infection) in AMD and AD contribute to toxic protein deposits, loss of homeostatic protein clearance, and progressive neurodegeneration [3][4][5][6][7][8][9][10][11].Neuroinflammation also provokes persistent immune response, which participates in further brain and macular damage. However, studies using anti-inflammatory therapy in AD and in AMD have yielded small, mixed or inconclusive results [12][13][14][15].Toxic protein accumulation: in AMD, drusen, (lipoprotein deposits between the basal lamina and the retinal pigment epithelial layer, RPE) and lipofuscin (from inefficient protein clearance) [3,4,13] and in AD, extracellular and intracellular amyloid and complement and intracellular tau, (because of breakdown of the blood-brain barrier from reactive oxygen species, inflammation, or local or systemic infection), may be slow burners in chronic inflammation and its sequelae [5,6,16] However, cognitive issues, (memory and learning) in AD may precede amyloid plaque and tau fibrillar aggregates by months or longer [5].
…”
mentioning
confidence: 99%
“…The global prevalence of AMD in 2020 is projected to be 196 million people [1] and that of Alzheimer's disease was 50 million in 2017 [2]. Chronic oxidative stress and neuroinflammation from aging, injury, and individual risk factors (smoking, hypertension, arteriolosclerosis, obesity, dietary indiscretion, chronic anticholinergic use, and latent infection) in AMD and AD contribute to toxic protein deposits, loss of homeostatic protein clearance, and progressive neurodegeneration [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%